Diskursus Kampung Restorative Justice Dan Eksistensi Peradilan Adat Di Provinsi Jambi - Kurniawan, Ardian; Marwendi, Reza Okva; Yusuf, M. Yusuf; Aiman, Muhammad; Tauvani, A. Yuli (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2024)
This research delves into the discourse related to village restorative justice and customary law in the Province of Jambi in the context of the diversity of authority shifts between modern legal approaches and existing legal traditions. The research background refers to conceptual differences and perspectives on dispute resolution between the state and customary law. To examine the relationship between the concept of restorative justice and customary justice, this study employs a qualitative approach by conducting in-depth interviews with representatives from the prosecution, community leaders, as well as traditional leaders in several restorative villages in the Province of Jambi. The literature review involves a profound understanding of restorative justice, customary justice, and the interaction between state law and customary law. The research findings highlight the conflicts and convergences between the restorative justice approach and the existence of customary justice. Conflicts arise in the interpretation of rights, obligations, and authority held by each system. However, this research also reveals the potential synergy between these two approaches in resolving disputes with a more holistic and contextual approach. The findings of this research indicate the importance of dialogue and collaboration between the state and customary law in developing initiatives such as village restorative justice. In the context of the Province of Jambi, wise integration of state and customary law can bring benefits for the preservation of cultural values as well as the fulfillment of individual and community rights.